Development of an in vitro system to study oral biofilms in real time through impedance technology: validation and potential applications. Issue 1 (1st January 2019) - Mira, Alex; Buetas, Elena; Rosier, Bob; Mazurel, Danuta; Villanueva-Castellote, Álvaro; Llena, Carmen; Ferrer, Maria D.
ABSTRACT: Background and objectives : We have developed a standardized, easy-to-use in vitro model to study single- and multiple-species oral biofilms in real time through impedance technology, which elucidates the kinetics of biofilm formation in 96-well plates, without the requirement for any further manipulation. Design and Results: Using this system, biofilms of Streptococcus mutans appear to be sugar-dependent and highly resistant to amoxicilin, an antibiotic to which this oral pathogen is highly sensitive in a planktonic state. Saliva, tongue and dental plaque samples were also used as inocula to form multiple-species biofilms. DNA isolation and Illumina sequencing of the biofilms showed that the multi-species biofilms were formed by tens or hundreds of species, had a similar composition to the original inoculum, and included fastidious microorganisms which are important for oral health and disease. As an example of the potential applications of the model, we show that oral biofilms can be inhibited by amoxicilin, but in some cases they are induced by the antibiotic, suggesting the existence of responders and non-responders to a given antibiotic. Conclusions: We therefore propose the system as a valid in vitro model to study oral biofilm dynamics, including their susceptibility to antibiotics, antiseptics or anti-adhesive compounds.